Ethanol Production on Jackfruit Seeds by Selected Fungi and Yeast from Loog-pang - Ochaikul*, Duangjai; Noiprasert, Nisakorn; Laoprasert, Wipawadee; Pookpun, Sasima (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Ethanol production from jackfruit seeds was carried out by using fungal strains isolated from tankoji(loog-pang). These were Rhizopus oryzae MNT 006, Aspergillus oryzae MNT 029, Amylomyces rouxii MNT 037 and Saccharomyces cerevisiae YRK 017. Fermentation sugar production from jackfruit seeds starch by 3 fungal strains was examined. Then the fermentable sugars produced so were tested as substrates for fermentation by S. cerevisiae YRK 017 to produce ethanol. The results showed that A. rouxii was the most effective organism for producing reducing sugar. Ethanol production process was studied on separated hydrolysis and fermentation (SHF) process and simultaneous saccharification and fermentation (SSF) process. The jackfruit seeds starch fermented by SHF process produced higher yield of ethanol than that from SSF process. Keywords: ethanol production, jackfruit seed, separated hydrolysis and fermentation, simultaneous saccharification and fermentation E-mail: kodaungj@kmitl.ac.th